A bimanual manipulation technique for establishing the CR position - Martinović Željko (Serbian Medical Society - Dental Section, Belgrade, 2003)
In this work, we demonstrate a modern concept of the cr position. We analyze main characteristics of the central relation position from mechanical and physiological aspects. Furthermore, we discuss the bimanual manipulation technique on the lower jaw, required for balancinh procedures or investigation of premature contacts. Since an effective manipulation technique requires a combination of gentle yet firm digital pressure in a cranial direction., with a good sense of timing, clinician needs to have ! a mental picture of what is happening in TMJs and how are muscles affected by different movements and pressure. We have specifically presented instructions on firm-digital-pressure test. With this test it is possible to effectively verify the consistency of a certain cr position as well as to exclude the intra-articulating problems. Most of the time when the patient is tense and uncooperative, it is because the pressure is applied on the mandibule before the lower jaw is gently positioned into its most cranial position with separate dental arches. It seems, at least for now, that there are no procedures which can provide so much practical benefit for both the clinican and the patient at the same time, as can routine registration of the cr position and verification of its accuracy.